PEMANFAATAN POTENSI HASIL TANGKAP NELAYAN MENJADI OLAHAN KERUPUK IKAN KATAMBAK DI DESA TANJUNG LUAR KECAMATAN KERUAK KABUPATEN LOMBOK TIMUR - Furqon, Nazilil; Cahyanti, Lina; Paramaswari, Gusti Ayu Made; Hapsari, Gusti Ayu Ratih; Pratama, Agung Naufal; Anggara, Ami; Kholvi, Nifa; Buana, Panji Jayadi; Fatmala, Isni Nadia; Kholissurahman, Kholissurahman; Abidin, Zaenal (Universitas Mataram, 2023)
Fish potential can be used as one of the foods. This aims to train the community to process fish catches into value-added products, namely fish crackers. Fish crackers, dried snacks made from catambak fish meat, tapioca flour, garlic and flavorings are not widely known by the public. Therefore, we make and introduce the catambak fish cracker product to the public in order to gain popularity because of its enjoyment and delicacy. The inclusion of catambak fish in this business has considerable potential, given its high protein content and economic significance.